Digitale Lehr- und Lernangebote in der medizinischen Ausbildung - Kuhn, Sebastian; Frankenhauser, Susanne; Tolks, Daniel (Bundesgesundheitsblatt, Gesundheitsforschung, Gesundheitsschutz, 2018)
The current choice of digital teaching and learning formats in medicine is very heterogeneous. In addition to the widely used classical static formats, social communication tools, audio/video-based media, interactive formats, and electronic testing systems enrich the learning environment.For medical students, the private use of digital media is not necessarily linked to their meaningful use in the study. Many gain their experience of digital learning in the sense of “assessment drives learning”, especially by taking online exams in a passive, consuming role. About half of all medical students can be referred to as “e-examinees” whose handling of digital learning is primarily focused on online exam preparation. Essentially, they do not actively influence their digital environment. Only a quarter can be identified as a “digital all-rounder”, who compiles their individual learning portfolio from the broad range of digital media.At present, the use of digital media is not yet an integral and comprehensive component of the teaching framework of medical studies in Germany, but is rather used in the sense of a punctual teaching enrichment. Current trends in digital teaching and learning offerings are mobile, interactive, and personalized platforms as well as increasing the relevance of learning platforms. Furthermore, didactical concepts targeting the changed learning habits of the students are more successful regarding the acceptance and learning outcomes. In addition, digitalization is currently gaining importance as a component in the medical school curricula.